Does regulation matter? A cross‐national analysis of the impact of gun policies on homicide and suicide rates. Issue 4 (21st December 2018) - Hurka, Steffen; Knill, Christoph
Abstract: In this contribution, we evaluate the effectiveness of firearm regulations in curbing the number of homicides and suicides committed both with and without firearms. We develop a gun control index that enables us to compare the restrictiveness of firearm regulations across time and space. We model the effects of gun control on figures of (gun) homicide and (gun) suicide gained from public health records in 16 West European countries between 1980 and 2010. We thus shift the analytical focus away from the United States, which can be considered an extreme case in many ways and analyze the effects of gun control in a least likely setting: a world region in which gun control is comparably strict to begin with. Our analysis demonstrates that stricter gun control entails a strong and robust negative effect not only on homicides and suicides committed with firearms, but also on overall homicide and suicide rates.